2019
DOI: 10.3390/w11071384
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Sea Level Rise and River Discharge on the Hydrodynamics Characteristics of Jakarta Bay (Indonesia)

Abstract: Jakarta city has been vulnerable to sea level rise and flooding for many years. A Giant Seawall (GSW) was proposed in Jakarta Bay to protect the city. The impacts of sea level rise and river discharge on the tidal dynamics in Jakarta Bay and flooding areas in Jakarta city were investigated using the finite-volume coastal ocean model (FVCOM). Model results showed that the bay is diurnally dominated by the K1 tidal component. The diurnal tides propagate westward, while the semidiurnal tides propagate eastward in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…From the Last Deglaciation to the Early Holocene, sea level in Sundaland rose rapidly (Geyh et al, 1979; Sathiamurthy & Voris, 2006). This likely caused an impeded drainage and rising groundwater level in the areas of present‐day Borneo, Sumatra and the Malaysia Peninsula (Sathiamurthy & Voris, 2006; Surya et al, 2019). In combination with increasing precipitation in Borneo (Section 4.2.2), it led to waterlogged conditions in Katingan, which allowed peat to accumulate rapidly (Dommain et al, 2011, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the Last Deglaciation to the Early Holocene, sea level in Sundaland rose rapidly (Geyh et al, 1979; Sathiamurthy & Voris, 2006). This likely caused an impeded drainage and rising groundwater level in the areas of present‐day Borneo, Sumatra and the Malaysia Peninsula (Sathiamurthy & Voris, 2006; Surya et al, 2019). In combination with increasing precipitation in Borneo (Section 4.2.2), it led to waterlogged conditions in Katingan, which allowed peat to accumulate rapidly (Dommain et al, 2011, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…From the Last Deglaciation to the Early Holocene, sea level in Sundaland rose rapidly (Geyh et al, 1979;Sathiamurthy & Voris, 2006). This likely caused an impeded drainage and rising groundwater level in the areas of present-day Borneo, Sumatra and the Malaysia Peninsula (Sathiamurthy & Voris, 2006;Surya et al, 2019).…”
Section: Responses Of the Katingan And Kampar Peninsula Peatlands To ...mentioning
confidence: 99%
“…The skill range varies in a similar pattern for all domains; as we can see in 10 km 2 domain, the index of agreement (skill) range is 0.975 to 0.988, while the 20 km 2 domain is 0.965 to 0.987 next one, the 25 km 2 domain is 0.976 to 0.987, and the last is the 30 km 2 domain in the 0.971 to 0.987 range. Surya et al, (2019) proposed a statistical method for assessing model skill in the context of verification. This skill represents the degree of divergence between prediction and observation data.…”
Section: Comparison Of Model Extent and Grid Sizementioning
confidence: 99%
“…Therefore, it can be concluded that the effect is negligible due to employing a hydrodynamic-only modeling scheme. A study by Surya et al (2019) demonstrates that the influence of river discharge affects the tidal component solely at the river mouth, while the overall study area remains unaffected by this river discharge. However, it should be noted that this boundary may exhibit significant alterations if a sediment module is incorporated into future studies.…”
Section: Comparison Of Boundary Conditionmentioning
confidence: 99%
See 1 more Smart Citation